The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.22237/jotm/1285891320
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between measures of operations efficiency and financial success of truckload motor carriers: An empirical analysis

Abstract: This research paper examines the statistical relationship between clay to day performance and effi­ ciency measures and financial performance in the motor carrier industry. Key findings are that carriers with more miles per tractor per year, a larger average length of haul, more revenue per mile, and more revenue per tractor per week tend to perform better financially as measured in three separate models by operating ratio, return on assets, or return on equity. Unexpectedly, for the eight publicly traded carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Operational performance refers here to the operational efficiency of LSPs, i.e., to internal-facing measures of how efficiently an LSP uses its resources to perform its day-to-day service activities (Lai et al , 2002). The measures developed by Johnston (2010) were used in this research. In order to measure asset utilisation, the empty-mile percentage and the average load factor ( per cent) in both domestic and international shipments were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Operational performance refers here to the operational efficiency of LSPs, i.e., to internal-facing measures of how efficiently an LSP uses its resources to perform its day-to-day service activities (Lai et al , 2002). The measures developed by Johnston (2010) were used in this research. In order to measure asset utilisation, the empty-mile percentage and the average load factor ( per cent) in both domestic and international shipments were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the study of Perotti et al (2012), Italian LSPs reported only a minor effect on operational performance. This study examines five operational performance measures by Johnston (2010): empty-mile percentage, average transport performance, average length of haul and average load factor in domestic and international shipments. Johnston (2010) argues that motor carriers use these measures to manage day-to-day operations, and improvements in them can increase asset utilisation and ultimately financial performance.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…It indicates better operating performance and a high-profit margin (Coyle et al, 2011). Previous studies have also shown that several performance indicators might explain the operating ratio (Johnston, 2010). Therefore, we regressed the operating ratio on capacity utilisation scores obtained from Equation ( 16).…”
Section: Modified Cost-efficiencymentioning
confidence: 99%